2017
DOI: 10.1055/s-0037-1613674
|View full text |Cite
|
Sign up to set email alerts
|

Release of Prometastatic Platelet-Derived Microparticles Induced by Breast Cancer Cells: A Novel Positive Feedback Mechanism for Metastasis

Abstract: Circulating platelets and platelet-derived microparticles are regulators of cancer metastasis. In this study, we show that breast cancer cells induce platelet aggregation and lead to the release of platelet-derived microparticles. Although able to cause comparable aggregation, the highly aggressive MDA-MB-231 cells were more potent than the poorly aggressive MCF7 cells in inducing platelet-derived microparticles release, which was comparable to that promoted by thrombin. MDA-MB-231 cells were able to bind and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 25 publications
(35 reference statements)
0
29
0
Order By: Relevance
“…Washed human platelets were prepared from buffy‐coat bags collected the same day of the experiment, a previously described 23 . Briefly, the buffy‐coat was diluted with one‐fourth of its initial volume using a 9:1 solution of 4‐(2‐hydroxyethyl)‐1‐piperazineethanesulfonic acid (HEPES) buffer (10 mmol/L HEPES, 137 mmol/L NaCl, 2.9 mmol/L KCl, 12 mmol/L NaHCO3, pH 7.4) and citric acid/citrate/dextrose (152 mmol/L sodium citrate, 130 mmol/L citric acid, and 112 mmol/L glucose) and centrifuged at 120 g for 15 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Washed human platelets were prepared from buffy‐coat bags collected the same day of the experiment, a previously described 23 . Briefly, the buffy‐coat was diluted with one‐fourth of its initial volume using a 9:1 solution of 4‐(2‐hydroxyethyl)‐1‐piperazineethanesulfonic acid (HEPES) buffer (10 mmol/L HEPES, 137 mmol/L NaCl, 2.9 mmol/L KCl, 12 mmol/L NaHCO3, pH 7.4) and citric acid/citrate/dextrose (152 mmol/L sodium citrate, 130 mmol/L citric acid, and 112 mmol/L glucose) and centrifuged at 120 g for 15 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Washed human platelets were prepared from buffy-coat bags collected the same day of the experiment, a previously described. 23 Briefly, the buffy-coat was diluted with one-fourth of its initial volume using…”
Section: Human Platelet Preparationmentioning
confidence: 99%
“…Noteworthy, a bidirectional effect occurs as cancer cells can induce platelet activation and MV release; subsequently, a paracrine positive feedback mechanism is established, since MVs, taken up by cancer cells, potentiate the invasive phenotype through stimulation of migration [148,155]. Interestingly, although different cancer cells are able to induce platelet-derived MV release, only the most aggressive ones are responsive to MV action and, furthermore, only some subsets of MVs can positively feed back to cancer cells [155]. These findings suggest that i) cancer/platelet interplay is complex and strongly dependent on features of tumor cell type and ii) composition of MVs may differ depending on the stimulus given to platelets [155].…”
Section: Platelet Microvesicle-derived Mirnasmentioning
confidence: 99%
“…Interestingly, although different cancer cells are able to induce platelet-derived MV release, only the most aggressive ones are responsive to MV action and, furthermore, only some subsets of MVs can positively feed back to cancer cells [155]. These findings suggest that i) cancer/platelet interplay is complex and strongly dependent on features of tumor cell type and ii) composition of MVs may differ depending on the stimulus given to platelets [155]. These findings may clarify discrepancies observed by authors in studies using different platelet preparations, agonists and cancer cell types.…”
Section: Platelet Microvesicle-derived Mirnasmentioning
confidence: 99%
“…Another interesting issue is the ability of cancer cells to educate PLTs. Zarà et al demonstrated that breast cancer cell lines—highly aggressive MDM-MB-231 and MCF7 could educate PLTs to produce PEVs in an amount similar to that after thrombin activation [ 96 ]. Next, those PEVs were co-cultured with cancer cells to investigate if the newly formed PEVs impact cells.…”
Section: Pevs In Cancer Progressionmentioning
confidence: 99%